(untitled) (Biological Sciences - PJSIR, 2006)
The effect of short waves of electromagnetic energy on the lipid composition of peanut oil was studied when peanut seeds were roasted in a microwave oven. The results showed that heat treatment (in microwave oven) caused a slight change in nutritional quality of the oil in respect of fatty acids. Unsaturated and polyenoic fatty acids decreased with the increase of monounsaturated fatty acids in the oil of microwave heated peanut seeds. The oil extracted from the seeds before microwave roasting contained capric, lauric and myristic acids in traces. The oil contained 8.2% palmitic acid, 3.9% stearic acid, 59.87% oleic acid, 22.9% linoleic acid, 1.3% linolenic acid, and 3.7% arachidic acid. The microwave roasted peanut seed oil showed some changes in the fatty acids composition as stearic, linoleic, lino- lenic and arachidic acids reduced with the increase in the concentrations of oleic, capric, lauric and myristic acids.